'Yang Satu' dan Tanggung Jawab terhadap 'Yang Lain': Kritik terhadap Egologi dari Sudut Pandang Etika Levinasian - Simon, Untara (Institutum Ioannis Mariae Vianney Surabayanum, 2023)
This text wants to show that the idea of unity can be a serious problem in a multicultural society. In a multicultural society, there are many differences that cannot be relativized. In this kind of situation, The Other cannot simply be merged into The One. According to Levinas, there is a long history that shows that The One tries to absolutize itself and eliminate The Other. This condition appears in Platonism and Christianity. Facing this situation, Levinas offers an ethical attitude towards The Other as a willingness to take absolute responsibility. The method used in this research is the metaanalysis method. From this research, we show that in Levinas’s Ideas, the worship of The One is the root of disrespectful attitudes towards The Other in its otherness. From there, this research shows that Levinas’s Idea of responsibility towards The Other which appears in the ethics of the face is an alternative idea to fight the authoritarianism that posibly arise from the idea of unity.